Russian Energetic Industry Enterprises: Social Orientation of the Information Management - GAISINA, Lutsiya M.; KOLESNIKOVA, Olga I.; MEDVEDEVA, Alena V.; FAYRUZOVA, Angela R.; EFIMENKO, Evgeniy L.; LOPATINA, Elena V. (Journal of Environmental Management and Tourism; Vol 8 No 5 (2017): JEMT Volume VIII Issue 5(21) Fall 2017DO - 10.14505//jemt.v8.5(21).15, 2018)
An effective organization management system includes not only the organizational structure conforming the technological processes’ features but the optimal structure of the informative, communicative, social, managerial interactions among the subdivisions. The social orientation of the managing impacts in the enterprise scope may be defined by the sociological diagnostics methods by the special indices that characterize social properties of management system.Information is the main source and product of any managerial process that is why the analysis of the management system effectiveness assessment is impossible without the analysis of the information exchange systems’ assessment. The main methods of the social orientation definition are based on the communicative and the information exchange system analysis in the organization, the managerial social effectiveness and the managerial solutions are being defined, the workers’ opinions about the managerial system quality, the satisfaction with the managerial system functionality are being analyzed, the labor motivation is being assessed.